2017
DOI: 10.1371/journal.pone.0181837
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated mortality in the era of antiretroviral therapy scale-up – Nairobi, Kenya, 2015

Abstract: BackgroundDeclines in HIV prevalence and increases in antiretroviral treatment coverage have been documented in Kenya, but population-level mortality associated with HIV has not been directly measured. In urban areas where a majority of deaths pass through mortuaries, mortuary-based studies have the potential to contribute to our understanding of excess mortality among HIV-infected persons. We used results from a cross-sectional mortuary-based HIV surveillance study to estimate the association between HIV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
1
8
1
2
Order By: Relevance
“…The greater vulnerability of this group should draw the attention of healthcare professionals, regarding the inclusion and retention in healthcare services of PLHIV [ 9 ]. A study in Kenya has shown a 4-fold risk of death in PLHIV when compared to non-infected individuals, despite a 73.6% ART coverage [ 23 ]. In this study, 71% of reported PLHIV between 2006 and 2014 had started ART, with a significant tendency to increase the proportion of PLHIV receiving ART in the period.…”
Section: Discussionmentioning
confidence: 99%
“…The greater vulnerability of this group should draw the attention of healthcare professionals, regarding the inclusion and retention in healthcare services of PLHIV [ 9 ]. A study in Kenya has shown a 4-fold risk of death in PLHIV when compared to non-infected individuals, despite a 73.6% ART coverage [ 23 ]. In this study, 71% of reported PLHIV between 2006 and 2014 had started ART, with a significant tendency to increase the proportion of PLHIV receiving ART in the period.…”
Section: Discussionmentioning
confidence: 99%
“…The surveillance system found higher overall estimated HIV positivity than the Spectrum model ( 28 ). Female cadavers had higher positivity rates than male cadavers, whereas the Spectrum model predicts higher postmortem HIV positivity among men than women (because of the lower estimated coverage of ART among men than women) (Table 2).…”
Section: Evaluation Findingsmentioning
confidence: 84%
“…In 2015, an HIV-related mortuary surveillance system was piloted in Nairobi to determine HIV positivity among cadavers, annual cause-specific mortality rates, and annual HIV-specific mortality rates ( 27 , 28 ). Sample size calculations were performed to determine the number of specimens required to measure HIV-related deaths with prevalence as low as 5% of all deaths and the approximate duration of data collection.…”
Section: Hiv-related Mortuary Surveillance System In Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there is compelling evidence that maintaining the rates of diagnosis, treatment and, crucially, suppression of viral load required to keep HIV a manageable, non-transmittable condition remains challenging. Analysis of mortuary-based HIV surveillance data in Nairobi shows that although 73.6% of adults living with HIV are on treatment, which should be leading to a palpable decrease in mortality, their risk of death is still more than four times higher than those uninfected (Young et al 2017). This is somewhat unexpected given that ART has been shown to dramatically increase life-expectancy in lower-income countries (Nsanzimana et al 2015).…”
Section: Aids After Artmentioning
confidence: 99%